2023
DOI: 10.1039/d2py01414a
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of poly(n-butyl acrylate)-POSS copolymers via dynamic urea exchange enables self-healing, reprocessing and shape recovery

Abstract: In this contribution, we reported a novel approach to crosslink the linear poly(n-butyl acrylate)-POSS copolymers via dynamic urea exchange reaction. First, the linear copolymers of n-butyl acrylate, POSS acrylate with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…(h) Reprocessing ability of T 10 -UPy 10 . (i) Comparison of the E and T h among state-of-art HGPMs ,,, with T 8 -UPy 8 , T 10 -UPy 10 , and T 12 -UPy 12 . Our study demonstrated the combination of high E with relatively low T h .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(h) Reprocessing ability of T 10 -UPy 10 . (i) Comparison of the E and T h among state-of-art HGPMs ,,, with T 8 -UPy 8 , T 10 -UPy 10 , and T 12 -UPy 12 . Our study demonstrated the combination of high E with relatively low T h .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, these amorphous samples show exceptional reprocessing ability at a relatively low temperature within minutes even though they are completely broken (Figure h). To date, many studies ,,, have been dedicated to exploiting HGPMs with lower T h and higher E (Figure i), the topological effects caused by POSS cage size and/or symmetry simultaneously enhanced the mechanical and healable properties in larger POSS-based hybrid glassy polymeric materials, offering a novel and intriguing methodology in designing HGPMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation